2021
DOI: 10.3389/fmed.2021.749588
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of SARS-CoV-2 Infections From Other Viral Respiratory Infections by Scent Detection Dogs

Abstract: Background: Testing of possibly infected individuals remains cornerstone of containing the spread of SARS-CoV-2. Detection dogs could contribute to mass screening. Previous research demonstrated canines' ability to detect SARS-CoV-2-infections but has not investigated if dogs can differentiate between COVID-19 and other virus infections.Methods: Twelve dogs were trained to detect SARS-CoV-2 positive samples. Three test scenarios were performed to evaluate their ability to discriminate SARS-CoV-2-infections fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 41 publications
0
45
0
Order By: Relevance
“…A volume of 100 μl per sample was pipetted onto a cotton swab (for saliva and urine) or the cotton pad that was used to acquire the sweat sample itself was placed into a 4 ml glass tube and placed in a device called “Detection Dog Training System” (DDTS, Kynoscience UG, Hörstel, Germany) for training and testing as described in our previous studies ( 3 , 4 , 9 ). The DDTS allows for rapid, automatic, randomized, trainer-bias devoid and double-blind sample presentation ( 3 , 4 , 9 ). To verify the recorded results of the DDTS the dogs were filmed during testing and the videos were analyzed manually.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A volume of 100 μl per sample was pipetted onto a cotton swab (for saliva and urine) or the cotton pad that was used to acquire the sweat sample itself was placed into a 4 ml glass tube and placed in a device called “Detection Dog Training System” (DDTS, Kynoscience UG, Hörstel, Germany) for training and testing as described in our previous studies ( 3 , 4 , 9 ). The DDTS allows for rapid, automatic, randomized, trainer-bias devoid and double-blind sample presentation ( 3 , 4 , 9 ). To verify the recorded results of the DDTS the dogs were filmed during testing and the videos were analyzed manually.…”
Section: Methodsmentioning
confidence: 99%
“…With samples of acute coronavirus disease 2019 (COVID-19)-patients, several research groups have shown a detection sensitivity close to 95% and a specificity of 97% for confirmed cases (positive RT-PCR) vs. SARS-CoV-2-negative subjects ( 3 – 8 ). In addition, our group has shown that dogs can differentiate SARS-Co-V-2 infected material not only from control samples but also from samples of patients with other respiratory viral infections, including other coronaviruses ( 9 ). It is thought that the specific odor of an infection is composed of a unique pattern of volatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that trained dogs can also distinguish SARS-CoV-2-infections from other viral infections with mean specificities above 90% [10].…”
Section: Discussionmentioning
confidence: 99%
“…in one study, were able to differentiate SARS-CoV2 infections from infections with other novel coronaviruses, influenza viruses, parainfluenza viruses, an adenovirus, a rhinovirus, a metapneumovirus (HMPV), and respiratory syncytial virus (RSV)—all etiological agents common to respiratory tract infections ( 65 ), thus demonstrating the potential for BMDDs to aid in the triage and differential diagnosis process.…”
Section: Introductionmentioning
confidence: 99%
“…Training aids developed for MDDs can consist of direct capture of bodily fluids (e.g., urine, blood plasma, blood serum, sputum, nasal swabs, saliva, feces) or human scent (breath, sweat, skin/body odor) captured onto a substrate (clothing, gauze pad, cotton ball, worn surgical mask) from infected and uninfected patients ( 65 , 77 ). The canine training aid(s) selected for a BMDD is of utmost importance as this decision will affect the canine’s ability to detect the target odor (either disease or pathogen) and may influence the canine’s ability to generalize to other target odors, e.g., novel patient samples, and discriminate from other similar pathogens, e.g., non-pathogenic strains of a virus or bacteria, both highly desirable BMDD skills.…”
Section: Introductionmentioning
confidence: 99%